Association between Obesity and Metabolic Anomalies in a Population in Eastern Algeria - Dalichaouche-Benchaoui, Souhaila; Abadi, Nourredine (Jordan Medical Journal, 2022)
Obesity is defined by an excess of fat and can be considered as a heterogeneous, multifactorial phenotype, determined by genetic factors, environmental factors, and gene-environment interaction. A high body mass index is an important risk factor in the development of much comorbidity dominated by metabolic disorders and cardiovascular diseases. The objective of this work was to describe the obesity (BMI≥30 kg/m2) and metabolic profile of adults in Constantine. A descriptive cross-sectional survey was conducted and anthropometric and clinical examinations were performed. Biochemical assays (fasting glucose, triglycerides, total cholesterol, HDL and LDL cholesterol) were performed. In total, 1,143 subjects participated, with the sample comprised of 41.3% men and 58.7% women. The mean body mass index was 27.22, and the overall prevalence of obesity in the sample was 30.9%. Abdominal obesity by the International Diabetes Federation (IDF) was present in 68.15% (83.5% women vs. 46.4% men). The incidence of type 2 diabetes was 42% in the obese subjects. The average number of metabolic complications was greater in the obese than non-obese subjects. Binary logistic regression analysis showed that in men the association between hypercholesterolemia, dyslipidemia, and hypertriglyceridemia was the same, regardless of the participants’ BMI. This association increased with BMI in women. With regard to hyperglycemia, the association increased with BMI in men but much more in women. Metabolic abnormalities are more frequent in obese people, increasing their cardiovascular risk, and thus urgent preventive actions need to be taken.